REALITY: A Philosophical Poem - Smith, John Clark (Journal of Dharma, 2022)
Reality has no borders. Humans thought borders and made territories. In reality, no lines separate. All of it belongs to all. Reality is not one or two or any number. In reality all are not one or two or any number. In reality, there is no sameness, or difference, neither peace nor conflict. One is not the beginning or the end. Reality transcends the many and the one.